THE LABOUR SHARE IN HOUSEHOLDS’ INCOME INEQUALITY IN ROMANIA - Bianca VEZENTAN; Olimpia NEAGU (Annals of the University of Oradea: Economic Science)
The aim the paper is to analyse the relationship between the labour share in the households’ income and inequality expressed by Gini coefficient in Romania during 1997- 2020. Based on data from National Institute of Statistics of Romania, we provide evidence that high shares of labour income in total households’ income are associated with high values of estimated Gini coefficient and labour and wages share could explain households’ income inequality. We also highlighted the link of income inequality and income labour share to economic growth. Economic growth is associated with reducing levels of income inequality only in short periods of time. Policy makers should give attention to the evolution of labour share in the total income of households. Appropriate public policy measures regarding the improvement of labour market outcomes are required in order to prevent the rise of wage inequality